2012
DOI: 10.1007/s10620-012-2374-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Concomitant Enteral Nutrition Therapy and Infliximab for Maintenance Treatment of Crohn’s Disease in Adults

Abstract: BackgroundOne of the problems associated with infliximab (IFX) treatment for Crohn’s disease (CD) is loss of response during maintenance therapy.AimsThe aim of this multicenter, retrospective, cohort study was to determine whether enteral nutrition (EN) added to the IFX therapy regimen is effective for maintaining remission in adult CD patients.MethodsPatients with CD who had started IFX therapy between April 2003 and March 2008 at any one of the seven participating medical centers and who met the following in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 29 publications
1
65
1
1
Order By: Relevance
“…Parenteral nutrition of patients with IBDs shows numerous adverse side effects with increased risk of systemic infections; and most importantly is not beneficial for IBD control [96,97]. No positive effects of parenteral nutrition on maintenance of remissions and in its induction were demonstrated in both CD and UC.…”
Section: Enteral Feeding Mechanism Of Actionmentioning
confidence: 99%
“…Parenteral nutrition of patients with IBDs shows numerous adverse side effects with increased risk of systemic infections; and most importantly is not beneficial for IBD control [96,97]. No positive effects of parenteral nutrition on maintenance of remissions and in its induction were demonstrated in both CD and UC.…”
Section: Enteral Feeding Mechanism Of Actionmentioning
confidence: 99%
“…The minimum amount of enteral nutrition support was reported to be ⩾600 kcal/ day in the study by Sazuka and colleagues [Sazuka et al 2012]. In all the studies, patients were allowed to receive an oral diet to supplement their Hirai et al 2013;Sazuka et al 2010;Tanaka et al 2006] were given an overall global grade of 'moderate', while the fifth study [Yamamoto et al 2010] was given a score of 'strong' because of its prospective nature (Table 2).…”
Section: Study Detailsmentioning
confidence: 99%
“…The overall rate of clinical remission was assessed in four studies [Hirai et al 2013;Sazuka et al 2010;Tanaka et al 2006;Yamamoto et al 2010 (Figure 2). The number needed-to-treat with combination therapy of infliximab and specialized enteral nutrition to maintain clinical remission is four patients.…”
Section: Overall Clinical Remissionmentioning
confidence: 99%
“…However, 25–40% of patients with CD with a good initial response to anti-TNF-α show loss of response during maintenance therapy mostly within the first 6 months after induction [5, 6]. Several studies have reported that concomitant therapies such as immunomodulators and an elemental diet are useful for preventing the loss of response to anti-TNF-α within a few months [7, 8]. These findings suggest that the optimization of therapy is important for improving prognosis in patients with CD.…”
Section: Introductionmentioning
confidence: 99%